2022
DOI: 10.30773/pi.2021.0373
|View full text |Cite
|
Sign up to set email alerts
|

Discrepancy Between Desired Time in Bed and Desired Total Sleep Time, Insomnia, Depression, and Dysfunctional Beliefs About Sleep Among the General Population

Abstract: Objective The aim of this study was to explore the factors that can influence the severity of insomnia in the general population. We also aimed to examine whether sleep effort mediates the association between dysfunctional beliefs about sleep or the discrepancy between desired time in bed and desired total sleep time (DBST) and insomnia severity in individuals.Methods A total of 387 participants enrolled in this e-survey study. The symptoms were rated using the insomnia severity index (ISI), Patients Health Qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(51 citation statements)
references
References 30 publications
0
46
5
Order By: Relevance
“…As the discrepancy is high, we can speculate that patients may suffer severe insomnia or a high level of dysfunctional beliefs about sleep. A recent study reported that the severity of insomnia was influenced by depression, sleep preoccupation, dysfunctional sleep beliefs, and DBST index in the general population [24]. The first objective in this replication study is to investigate the usefulness of DBST index again, since this concept isn't still valid.…”
Section: Concept Of the Dbst Index; The Discrepancy Between Desired T...mentioning
confidence: 99%
“…As the discrepancy is high, we can speculate that patients may suffer severe insomnia or a high level of dysfunctional beliefs about sleep. A recent study reported that the severity of insomnia was influenced by depression, sleep preoccupation, dysfunctional sleep beliefs, and DBST index in the general population [24]. The first objective in this replication study is to investigate the usefulness of DBST index again, since this concept isn't still valid.…”
Section: Concept Of the Dbst Index; The Discrepancy Between Desired T...mentioning
confidence: 99%
“…The DBST index seems related to the dysfunctional beliefs about sleep. Our previous studies [11][12][13] showed a correlation between the DBST index and rating scales for measuring dysfunctional beliefs about sleep. Although the severity of insomnia is the most powerful predictor of the DBST index, dysfunctional beliefs about sleep may also have an effect on it.…”
Section: Discussionmentioning
confidence: 93%
“…If they want to sleep for at least 6 hours (desired TST) and fall asleep early in the evening, they should wake up early in the As the name suggests, the discrepancy between desired TIB and desired TST index (the DBST index) reflects the discrepancy between one's desired hours of TIB and desired hours of TST. The concept of this index comes from this dysfunctional thinking regarding their sleep-wake cycle [11]. The desired TST can be determined by asking, "For what number of hours do you wish to sleep per day?"…”
Section: Concept 2: Discrepancy Between Desired Time In Bed and Desir...mentioning
confidence: 99%
See 1 more Smart Citation
“…The DBST index was defined as a difference in one’s desired time in bed from one’s desired total sleep time to measure one’s severity of insomnia [ 19 ]. Although it is a new concept used to easily assess an individual’s insomnia severity, we explored the usefulness of the DBST index among the general population.…”
Section: Methodsmentioning
confidence: 99%